KEKURANGAN VITAMIN A PADA KELOMPOK BAYI DAN FAKTOR YANG BERHUBUNGAN DI KABUPATEN BOGOR - Muherdiyatiningsih Muherdiyatiningsih; Nuning M. Kiptiyah; Muhilal Muhilal; Sri Martuti; Frank T. Wieringa; Marjoleine A. Dijkhuizen (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2003)
VITAMIN A DEFICIENCY AND ITS RELATED FACTORS IN INFANTS IN BOGOR DISTRICT.Background: Based on clinical indicators, vitamin A deficiency in Indonesia is not a public health problem because the prevalence of xerophthalmia has been decreased to 0.34%. But, this decrease has not been followed by a decrease of marginal deficiency of vitamin A in vulnerable groups, especially infants.Methods: The cross-sectional baseline study was conducted at Bogor District. The aim of the study was to collect information about the vitamin A status of the breastfed infant, and to look for a relationship between many factors related to it. The samples were 183 breastfed infants aged 2-0 months without chronic disease, congenital disease, severe PEM nor twins. The chi-square and the prevalence odds ratio (POR) at the 95% confidence interval were used to measure the association between variables. Multiple logistic regression analysis was used to measure the closest factors to infant's vitamin A status.Results: The study showed that 54.1% of breastfed infants were at risk of vitamin A deficiency. Based on bivariate analysis, there are two significant independent variables related to infants vitamin A status, which are maternal vitamin A status and infant infection status. Multiple logistic regression analysis showed that infection status is the closest factor to vitamin A deficiency in infants, followed by maternal vitamin A status and breast feeding frequency. There are no significant association between supplementary feeding, age, nutritional status and the infant's vitamin A status.Conclusions: Marginal vitamin A deficiency in infants aged 2-10 months is still a public health problem in the research area. The infection status is the closest factor to vitamin A deficiency in infants, followed by maternal vitamin A status and breast feeding frequency.Keywords: vitamin A deficiency, breast feeding, infection, complementary feeding, infant